Fetal Kidney Length: Can be a New Parameter for Determination of Gestational Age in 3rd Trimester - Yusuf, Nahid; Moslem, Fauzia; Haque, Jasmine Ara (TAJ: Journal of Teachers Association, 2009)
Ultrasound provides an accurate & objective method of determining fetal age in utero. A prospective study was done in 102 pregnant women after 30 weeks of pregnancy whose gestational ages were confirmed by early USG. (<24 weeks). The aim of this study was to establish a correlation between the fetal kidney length & gestational age in 3rd trimester. The mean length of fetal kidneys showed a linear correlation with gestational age. The mean fetal kidney length in mm approximates the gestational age in weeks in 3rd trimester as predicated by BPD, FL, AC & HC (P<0.001). Maternal height, weight & socioeconomic status did not show any effect on growth of fetal kidneys. The result obtained confirmed that measurement of fetal kidney length in mm can be used as an additional parameter for documentation of gestational age in 3rd trimester & also an early means of detection of abnormal renal development. doi: 10.3329/taj.v20i2.3078 TAJ 2007; 20(2): 147-150